Facile synthesis of graphene nano zero-valent iron composites and their efficient removal of trichloronitromethane from drinking water. (March 2016) - Chen, Haifeng; Cao, Yu; Wei, Enze; Gong, Tingting; Xian, Qiming
Abstract: Halonitromethanes (HNMs), as an emerging class of disinfection by-products containing nitrogen (N-DBPs) in drinking water, have possessed public health concerns. Two most studied materials, graphene and nanometer-sized zero-valent iron, have been successfully combined into binary nanocomposites (G-nZVI) via facile carbonization and calcinations of glucose and ferric chloride, which was used in the removal of HNMs from drinking water in this study. When the Fe/C mass ratio was 1:5, the as-prepared G-nZVI hybrids comprised numerous dispersed Fe 0 nanoparticles with a range of 5–10 nm in diameter. Batch experimental results indicated that the as-prepared G-nZVI could effectively remove trichloronitromethane (TCNM), a dominant in the group of HNMs from drinking water. About 99% of initial TCNM could be adsorbed and degraded under 60 mg/L G-nZVI dosage within 120 min. Kinetic studies indicated that the removal of TCNM by G-nZVI followed a pseudo first order rate (R 2  > 0.9). The degradation pathways of TCNM by G-nZVI nanocomposites might include dechlorination and denitration of TCNM. The Fe was in the form of iron oxides in the graphene material shape which was then restored to Fe 0 again via calcinations. These results indicated that the synthesized G-nZVI nanocomposites could be a powerful material to remove HNMs from drinking water. Highlights: A binary nanocomposite-graphene and nanometer-sized zero-valent iron (G-nZVI) has been facilely prepared. The as-prepared G-nZVI could effectively remove trichloronitromethane (TCNM) from water. The degradation pathway of TCNM by G-nZVI nanocomposites might include dechloration and denitration. The activity of the used G-nZVI could be restored by calcinations again.